Numerical Modeling of Functional Fatigue in NiTi Wires. Issue 1 (21st October 2015) - Osman, Muhammad; Bartel, Thorsten; Menzel, Andreas
Abstract Motivated by the high potential of shape memory alloys (SMA) in several industrial applications, we investigate the material response under cyclic loading. In particular, the focus is set on the modelling of functional fatigue, which results in the deterioration of the specific features of SMA. In fact, functional fatigue restricts SMA in terms of its applicability for real structures and workpieces. This necessitates the development of material models which take this phenomenon into account. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)